Hedging in English Social Science Research Articles: A Corpus-Based Comparison of Native and Turkish EFL Writers - Zekeriya Hamamcı (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2026)
Hedging plays a central role in academic writing because it enables researchers to present claims with appropriate caution and to situate their arguments in relation to earlier scholarship. This study compares hedging in English-language social science research articles written by native speakers of English and by Turkish scholars writing in English as a foreign language. Adopting a corpus-based contrastive design, the study examines 90 published research articles with WordSmith Tools. The corpus comprises 37,243 words in the Turkish EFL subcorpus and 38,349 words in the native-speaker subcorpus, with texts drawn from economics, education, law, and literature. The analysis considers both the overall frequency of hedges and their distribution across two rhetorically important parts of the article: the Introduction and the Discussion/Conclusion. Statistical analysis showed no significant difference in total hedge frequency between the two groups (p = .935). Native-speaker writers produced 866 hedges (4.38%), while Turkish EFL writers produced 868 (4.39%). The contrast emerges not in quantity, but in placement. Turkish writers used more hedging in Introductions, whereas native-speaker authors used more in Discussion and Conclusion sections, where interpretation and evaluation become more prominent. The findings indicate that both groups share a broad awareness of cautious academic positioning, yet differ in how they distribute that caution across the article. The study therefore suggests that research on hedging should consider rhetorical location alongside raw frequency. The results also point to the value of section-sensitive instruction in EAP and ESP writing classrooms.